Dante’s Self-Angelizing: A Prophecy of Egalitarian Transhumanism - Hall, Joshua (Labyrinth, 2020)
In this article, I argue that Dante's philosophical goal is what I term "self-angelizing," an ennobling philosophical education granting one the knowledge and power of an angel, which the medieval scholastics conceived as celestial intelligences. Dante's own path to self-angelizing begins in his early New Life, which approaches a living Beatrice as exemplar of terrestrial angels. Next, Dante's middle-period Banquet discusses following Beatrice into self-angelizing through an education in philosophical virtue. Finally, in his climactic Paradise, Dante performs his own self-angelizing. The upshot of this journey is Dante's prophecy of an egalitarian transhumanism.